2020
DOI: 10.1590/fst.19519
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of commercial pea protein isolate: effect of microbial transglutaminase and thermal processing

Abstract: In the studied commercial pea protein isolate (PPI) some physicochemical modifications are induced in the protein structure during its processing. That fact would result into a reduction of proteins techno-functional properties. It has been evidenced by Differential Scanning Calorimetry the protein denaturation what gives as a result poor gelling ability. Microbial transglutaminase (MTGase) was added at different concentrations to improve the gelation process at two different settings/thermal treatments to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Textural improvements using TG have also been reported for plant protein matrices for meat and seafood analogues, 22 bread, 23 heat-induced pea protein gels, 13,24 fermentation-induced mung bean gels, 20 soy protein cream cheese 16 and cheeses made from soy/peanut-dairy blends. 25 Yet these studies did not investigate fermentation-induced gels made from pea protein emulsions and have not evaluated the effect of TG in an acidic pea protein environment.…”
Section: Introductionmentioning
confidence: 90%
“…Textural improvements using TG have also been reported for plant protein matrices for meat and seafood analogues, 22 bread, 23 heat-induced pea protein gels, 13,24 fermentation-induced mung bean gels, 20 soy protein cream cheese 16 and cheeses made from soy/peanut-dairy blends. 25 Yet these studies did not investigate fermentation-induced gels made from pea protein emulsions and have not evaluated the effect of TG in an acidic pea protein environment.…”
Section: Introductionmentioning
confidence: 90%
“…In fish-based products, it increases the hardness of the product, improves the appearance and stability of the protein film and even decreases the caloric content. In addition to being able to be used in the sweets and confectionery industries to increase the texture and elasticity of the product and in plant-based, such as soy and wheat, to make tofu, bread, bakery products and pasta (Kuraishi et al, 2001;Kieliszek & Misiewicz, 2014;Moreno et al, 2020;Lerner & Benzvi, 2021;Schlangen et al, 2023).…”
Section: Transferasementioning
confidence: 99%
“…The NSI of SPC produced by the alcohol method is generally lower (<15%). Still, the NSI difference in the measurement results is very significant, which is mainly caused by the different degrees of protein denaturation caused by process conditions, such as leaching concentration (Peng et al, 2021), drying methods (Ghribi et al, 2015) and different modification methods (Sui et al, 2021;Moreno et al, 2020). Studies had found that the protein solubility of ethanol-treated lentil protein isolate was below 10% when 35~55% ethanol was applied and increased to approximately 30% when the water/ethanol ratio increased from 55 to 75% (Chang et al, 2019).…”
Section: Analysis Of Spc Raw Materials Characteristicsmentioning
confidence: 99%